Bioremediation of landfill gas under laboratory conditions / Navarani a/p Vejaratnam - Vejaratnam, Navarani (2009)

(untitled)
Per capita generation of municipal solid waste (MSW) in Malaysia has reached 1.3kg per day giving a total generation of more than 31000 tonnes daily. All the MSW collected are disposed into 260 landfills or dumps with 90% of the landfills being non-sanitary. Due to lack of proper gas collection facilities, almost all the methane produced are released passively to the atmosphere.Malaysian landfills produce 1.3-7.5 L/kg/year of methane gas. Since methane is 23 times more harmful as greenhouse gas than CO2, it is essential to mitigate its emission from landfills. One option to reduce methane emissions is to oxidize the methane to CO2 and water using “Biocover”. The objective of this study is to investigate various Biocover materials such as compost, for methane oxidation capabilities under tropical conditions and to establish suitable Biocover height for landfill application. Batch incubation experiments using Wheaton bottles revealed that compost was the best (Biocover) material compared to black soil and compost residue. It took the shortest duration (4 days) for complete methane oxidation. Subsequently 1-m high reactor columns were used to evaluate methane oxidation using compost and black soil. Fresh Biocover material and mixture of used + fresh Biocover material ranging from 10-100cm in height was tested for methane reduction. Column height of 60cm compost and 80 cm black soil took the shortest time for CH4 oxidation indicating optimum Biocover height. Column trials with mixture of 90cm used+10cm fresh Biocover materials exhibited highest CH4 oxidation capacity for both compost and black soil. The Biocover Performance Index (BPI) ranged from 1.04-2.60 x 103, where the latter value was for compost. Kinetics of methane oxidation and statistical analysis were performed to determine the efficiency of biocover material. CH4 oxidation rate for compost was 3 times and 9 times higher compared to black soil and compost residue,respectively. It is evident that the use of compost as biocover could reduce methane emission from landfills; however, field conditions would also influence the rate of oxidation.